Analysis of Computer Adaptive Testing in a Pathopharmacology Course. - Austin, Elizabeth N.; Henson, Amanda P.; Kim, Hee Jun; Ogle, Kathleen T.; Park, Hyunjeong (Journal of Nursing Education, 2021)
Background: The use of various textbook and testing options for nursing education presents opportunities and challenges for nurse educators and students. The use of computer adaptive testing enables students to study material, quiz themselves on that material, and increase their levels of content mastery. The purpose of this study was to describe the effect of one computer adaptive testing program into a course that combined pathophysiology and pharmacology in a baccalaureate prelicensure nursing program. Method: A retrospective correlational design was used to explore the relationships between (a) computer adaptive quizzing, (b) quiz completion, (c) mastery of content, and (d) a standardized, computer-based pathophysiology examination. Results: Positive correlations were found between (a) quizzes completed and mastery level (Positive correlations were found between (a) quizzes completed and mastery level (r =.605, p <.001), (b), quizzes completed and standardized test scores (r =.349, p =.020), (c) number of questions completed and mastery level (r =.636, p <.001), (d) questions completed and standardized test scores (r =.365, p =.015), and (e) higher mastery levels and standardized test scores (r =.400, p =.007). Conclusion: Computer adaptive quizzing provides students with opportunities to improve content mastery and provides more experience with computer-based testing. Computer adaptive quizzing provides students with opportunities to improve content mastery and provides more experience with computer-based testing. [[J Nurs Educ. 2021;60(3):155–158.]